Canagliflozin impairs T cell effector function via metabolic suppression in autoimmunity - BENJAMIN JENKINS (2023)
Autoimmune diseases are characterised by augmented T cell function, ultimately leading to chronic inflammation and tissue damage. Altered T cell function is supported by metabolic dysregulation in the setting of autoimmunity, therefore targeting immunometabolism by repurposing clinically approved metabolic modulators, such as those used to treat type 2 diabetes (T2D), is an attractive prospect. Canagliflozin – a member of the newest class of T2D drugs, sodium glucose co-transporter 2 (SGLT2) inhibitors – has known off-target effects including inhibition of mitochondrial glutamate dehydrogenase (GDH) and complex I of the electron transport chain. Importantly, these properties are not shared with other SGLT2 inhibitors, particularly dapagliflozin which has very limited off-target effects. The effects of canagliflozin on human T cell function are unknown. This study revealed that canagliflozin, but not dapagliflozin, compromised the proliferation and effector function of human T cells. The inhibitory effect of canagliflozin was underpinned by reduced T cell activation. Proteomic analysis revealed that canagliflozin mediates changes on a global scale, inhibiting various aspects of T cell fitness including metabolism, mitochondrial function and protein translation. Specifically, MYC inhibition emerged as a predicted upstream regulator of the canagliflozin-induced changes in protein expression. Compromised cellular metabolism was confirmed in canagliflozin-treated CD4+ T cells, whereby oxidative phosphorylation and glycolysis were markedly impaired following inhibition of GDH and complex I. Mechanistically, canagliflozin inhibits early T cell receptor signalling, which subsequently impacted the downstream activity of signalling proteins including ERK, mTOR and MYC. Importantly, canagliflozin treatment of T cells derived from patients with autoimmune disorders – rheumatoid arthritis and systemic lupus erythematosus – significantly impaired their effector function. Again, these changes were underpinned by perturbed cellular metabolism and diminished activation. Together, this work provides a foundation for the repurposing of canagliflozin as a treatment for autoimmune disease.